Genomic surveillance uncovers ongoing transmission of carbapenem-resistant Acinetobacter baumannii (CRAB) and identifies actionable routes of transmissions in an endemic setting. (23rd March 2023) - Ong, Sean Wei Xiang; Rao, Pooja; Khong, Wei Xin; Ong, Victor Yi Fa; Sridatta, Prakki Sai Rama; Thevasagayam, Natascha May; Ho, Benjamin Choon Heng; Ang, Brenda Sze Peng; De, Partha Pratim; Ng, Oon Tek; Marimuthu, Kalisvar
Abstract: Objective: In our center, previous infection prevention and control (IPC) resources were concentrated on multidrug-resistant organisms other than CRAB because the rate of CRAB was stable with no evidence of outbreaks. Triggered by an increase in the baseline rate of CRAB isolated in clinical cultures, we investigated horizontal transmission of CRAB to guide targeted IPC actions. Methods: We prospectively collected clinical data of patients with positive CRAB cultures. We identified genetic relatedness of CRAB isolates using whole-genome sequencing. Findings were regularly presented to the IPC committee, and follow-up actions were documented. Results: During the study period, 66 CRAB isolates were available for WGS. Including 12 clinical isolates and 10 environmental isolates from a previous study, a total of 88 samples were subjected to WGS, of which 83 were successfully sequenced and included in the phylogenetic analysis. We identified 5 clusters involving 44 patients. Genomic transmissions were explained by spatiotemporal overlap in 12 patients and by spatial overlap only in 12 patients. The focus of transmission was deduced to be the intensive care units. One cluster was related to a retrospective environmental isolate, suggesting the environment as a possible route of transmission. Discussion of these findings at multidisciplinary IPC meetings led to implementation of measures focusing on environmental hygiene, including hydrogen peroxide vapor disinfection in addition to terminal cleaning for rooms occupied by CRAB patients. Conclusions: We showed that WGS could be utilized as a "tool of persuasion" by demonstrating the presence of ongoing transmission of CRAB in an endemic setting, and by identifying actionable routes of transmission for directed IPC interventions.